Chaperonin TRiC/CCT Recognizes Fusion Oncoprotein AML1-ETO through Subunit-Specific Interactions - Roh, Soung-Hun (Biophys J, 2016)
AML1-ETO is the translational product of a chimeric gene created by the stable chromosome translocation t (8;21)(q22;q22). It causes acute myeloid leukemia (AML) by dysregulating the expression of genes critical for myeloid cell development and differentiation and recently has been reported to bind multiple subunits of the mammalian cytosolic chaperonin TRiC (or CCT), primarily through its DNA binding domain (AML1-175). Through these interactions, TRiC plays an important role in the synthesis, folding, and activity of AML1-ETO. Using single-particle cryo-electron microscopy, we demonstrate here that a folding intermediate of AML1-ETO’s DNA-binding domain (AML1-175) forms a stable complex with apo-TRiC. Our structure reveals that AML1-175 associates directly with a specific subset of TRiC subunits in the open conformation.